2018
DOI: 10.1186/s13041-018-0421-4
|View full text |Cite
|
Sign up to set email alerts
|

Systemic functional enrichment and ceRNA network identification following peripheral nerve injury

Abstract: Peripheral nerve injury is a worldwide clinical issue that impacts patients’ quality of life and causes huge society and economic burden. Injured peripheral nerves are able to regenerate by themselves. However, for severe peripheral nerve injury, the regenerative abilities are very limited and the regenerative effects are very poor. A better understanding of the mechanisms following peripheral nerve injury will benefit its clinical treatment. In this study, we systematically explored the dynamic changes of mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Besides, circRNA HDAC9 /miR-138 / Sirt1 was involved in synaptic dysfunction [54]. CeRNA analysis may offer promising insight into the mechanism of neuronal injury [55,56]. However, the evaluation of circRNA mediated ceRNA in underlying effect of depression remains ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, circRNA HDAC9 /miR-138 / Sirt1 was involved in synaptic dysfunction [54]. CeRNA analysis may offer promising insight into the mechanism of neuronal injury [55,56]. However, the evaluation of circRNA mediated ceRNA in underlying effect of depression remains ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study has examined the mRNA abundance of LIF in the injured rat sciatic nerve segments and demonstrated that LIF mRNA expression is upregulated at 1 day, 4 days, and 7 days after peripheral nerve injury and gradually recovered to the normal level at 14 days after nerve injury 13 . Rat sciatic nerve segments were further subjected to immunostaining to determine the protein abundance of LIF after nerve injury.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have screened differentially expressed genes in rat sciatic nerve segments after peripheral nerve injury, discovered enriched Gene Ontology (GO) terms, and found that LIF, a gene encoding leukemia inhibitory factor (LIF), is involved in the GO term “negative regulation of cell proliferation” 13 . LIF is a neurotrophic factor that supports the development and survival of neurons and rescues neuronal death after axotomy 14 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The sequences of miR-328a-3p were highly conserved in different species, including human (H. Sapiens) and rats (R. Norvegicus). Considering that we have obtained the transcriptome pro les and identi ed ceRNA networks of rats after peripheral nerve injury (33), here, we determined lncRNA-miR-328a-3p-mRNA interactions, constructed a miR-328a-3p-centered ceRNA network, and explored the temporal expression patterns of miR-328a-3p-associated lncRNAs and mRNAs in the injured sciatic nerves of rats. Following peripheral nerve injury, the expression levels of miR-328a-3p rst decreased, reaching a valley level at 4 days after nerve injury, and then gradually recovered to the uninjured level at 14 days (12).…”
Section: Discussionmentioning
confidence: 99%